1989
DOI: 10.1007/bf02270723
|View full text |Cite
|
Sign up to set email alerts
|

Competition and kin discrimination in colony founding by social Hymenoptera

Abstract: SummaryAfter mating, queens of social wasp and ant species sometimes band together to start a new colony cooperatively. I assume these queens sequentially encounter potential nest sites that may or may not already contain a queen. Whether to remain at a given site or to leave in hopes of finding a better site is modelled using dynamic programming. The results suggest that discriminating competitive ability is more valuable than discriminating kinship. Wasps, which have a high survival rate in transitions betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…In most ant species founding by pleometrosis, including L. niger, kinship is not a factor influencing queen association because the chance of encountering relatives is low. Nonacs (1989Nonacs ( , 1992 proposed that variance in competitive ability should favour conditional joining behaviour. In agreement with this prediction, laboratory experiments on L. pallitarsis showed that the joining decision of queens depends on the phenotype of potential cofoundresses, with queens preferentially joining lighter residents and lighter queens being more likely to leave nest sites when joined by others (Nonacs 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In most ant species founding by pleometrosis, including L. niger, kinship is not a factor influencing queen association because the chance of encountering relatives is low. Nonacs (1989Nonacs ( , 1992 proposed that variance in competitive ability should favour conditional joining behaviour. In agreement with this prediction, laboratory experiments on L. pallitarsis showed that the joining decision of queens depends on the phenotype of potential cofoundresses, with queens preferentially joining lighter residents and lighter queens being more likely to leave nest sites when joined by others (Nonacs 1992).…”
Section: Discussionmentioning
confidence: 99%
“…If queens can choose, they should always join a queen they can beat in the eventual fight for sole control of the colony 31 . Because queens vary in fighting ability 9,18,[23][24][25]32 , poor competitors should only join an association if their odds of success as a solitary foundress are even more dismal 9 .…”
Section: Who Should Queens Join?mentioning
confidence: 99%
“…Because queens vary in fighting ability 9,18,[23][24][25]32 , poor competitors should only join an association if their odds of success as a solitary foundress are even more dismal 9 . A model that incorporates survival chances (while searching for nest sites) and variable benefits of cofounding ( Table 2), predicts that ant queens should join any nest if the odds that they will die before joining a nest are high, but that otherwise they should discriminate by competitive ability 31 . Kinship is not a factor because the chance of encountering relatives is so low.…”
Section: Who Should Queens Join?mentioning
confidence: 99%
“…However, in several well-studied species, queen fighting or executions by workers eliminate all but one queen soon after the first workers emerge (Bartz and H611dobler 1982;Tschinkel and Howard 1983;Rissing and Pollock 1986;Peeters and Andersen 1989; for exceptions see H611dobler and Carlin 1985;Mintzer 1987). Since co-founding queens in these species are usually unrelated (Hagen et al 1988;Nonacs 1989) and probably cannot distinguish which queen is most likely to survive (Roisin 1993), pleometrosis appears to be an instance of cooperation driven by mutualism (Rissing and Pollock 1988;Nonacs 1992;Roisin 1993) or group selection (Mesterton-Gibbons and Dugatkin 1992). Studies on this phenomenon have sought to understand the conditions under which the advantages of group formation outweigh the disadvantages of competition among queens within groups.…”
Section: Introductionmentioning
confidence: 99%